A film review: the story behind miracle in cell no. 7 - Wajdi, Majid; Dewi, Ida Ayu Made Wulan Sukma; Riama, Pelita; Anwar, Ni Luh Gede Indah Aprilia; Dynata, Kayla Tabina; Widarwan, Kadek Candra Widyaswasti; Setyowati, Ratih (Yayasan Mitra Persada Nusantara, 2023)
Movies always have an impact on society based on the message they convey. The film's message has the potential to influence the audience's thinking and behaviour. This review examines the socioeconomic disparity depicted in the film Miracle in Cell No. 7 in order to highlight the message conveyed. The purpose of this review is to discover the conflicts shown in the film, as well as the messages included and packed by the filmmaker. The Robert N. Etman Media Text Framing Analysis model was used to analyze this study, which includes four research analysis tools: problem identification (defining the problem), causal interpretation (estimating the problem or source of the problem), moral evaluation (making a moral decision on the problem), and treatment recommendations (emphasizing problem solving) with a critical perspective within the Frankfurt School's critical theory paradigm. The findings of this study reveal that the components that depict conflict in this film are drawn from societal occurrences. Reviewers can use the framing model to uncover messages in the film, such as praiseworthy messages or good attitudes.